Pendidikan Karir Di SMK Muhammadiyah 7 Wonosegoro - Arrasyidin Arrasyidin (STIKes Ibnu Sina Ajibarang, 2024)
The aim of vocational education is to equip students with the skills necessary to be able to compete in the world of work. Vocational education has a priority, namely equipping students with knowledge, skills, and a work ethic so that they are able to compete in the current job market. This journal article will discuss the implementation of career education development strategies in vocational schools. This research uses a qualitative methodology known as a literature review approach. Based on research findings, career guidance programs in secondary schools provide balanced knowledge and experience to help students develop self-awareness, learn various career paths, improve decision-making abilities, and ultimately make career decisions independently. To encourage future professional fulfillment and success, vocational school and career guidance programs encourage independent career decision-making.